Irrationally elliptic closed characteristics on symmetric compact convex hypersurfaces in R^8 - Wang, Wei (Topological Methods in Nonlinear Analysis, 2023)
Let Σ be a C^3 compact symmetric convex hypersurface in R^8. We prove that when Σ carries exactly four geometrically distinct closed characteristics, then there are at least two irrationally elliptic closed characteristics on Σ.